New versus old: Implications of evolving diagnostic criteria for relapsing–remitting multiple sclerosis. (May 2019) - McNicholas, Nuala; Lockhart, Andrew; Yap, Siew M; O'Connell, Karen; Tubridy, Niall; Hutchinson, Michael; McGuigan, Christopher
The International Panel on Diagnosis of Multiple Sclerosis (MS) recently revised the 2010 McDonald criteria and made recommendations for revision, allowing for the earliest possible, accurate diagnosis of MS. For relapsing–remitting MS, positive, unmatched cerebrospinal fluid oligoclonal bands may substitute for dissemination in time. Symptomatic lesions, including brainstem and spinal cord, may demonstrate dissemination in space or in time if enhancing (with the exception of the optic nerve). Cortical and juxtacortical lesions are equivalent. In this retrospective analysis, we applied revised criteria to 250 patients previously diagnosed with relapsing–remitting MS according to 2010 criteria and assessed for change in diagnostic times. There was a significant improvement in time to diagnosis between 2010 and 2017 groups ( p  < 0.01). Median time to diagnosis according to McDonald 2010 was 7.4 months, compared with 2.3 months for McDonald 2017. Use of cerebrospinal fluid results most frequently resulted in a reduction in time to diagnosis. Symptomatic gadolinium-enhancing lesions led to earliest diagnostic times.